Adolescence - between childhood and adulthood - Richards, Martyn (Henry Stewart Talks, 2010)
Adolescents' moods, Ephebiphobia, Society's attitude to adolescence, Alcohol is safer than drugs?, Adolescents' self harm, Adolescents' mental health, Adolescents' pregnancy, Age of puberty, Hormones are to blame?, Teenage brain, Magnetic resonance imaging, The prefrontal cortex, Teenagers' poor decisions and judgment, Linking sports and cerebellum development, Key difference between teenagers and adults, Gender-based neuroscience and illness, Melatonin, Legal liability of teenagers, Why teens behave the way they do, 20th century versus 21st century thinking, Youth tribes and UK tribes, Myths exploded, Teenagers' bad press